Trancseding what is literally prescribed about Zakāh in Islam: A Fiqh-Economic Study - Irshaid, محمود عبد الكريم (Journal of King Abdulaziz University: Islamic Economics, 2022)
This study aims to explore the possibility of paying the monetary value instead of the in-kind value (zakāh of agricultural and livestock products) and paying it in the form of commercial offers. To this end, the study was guided by maqāṣid al-sharīʿa with a focus on who pays and benefits from zakāh dues. The researcher used inductive and deductive methods to justify the alternative of paying zakāh for agricultural products and livestock or the cash payment alternative, in addition to the payment of zakāh commercial offers instead of cash money. The researcher purposely used the analytical method to correlate the specifics and non-payment justifications to their maqāṣid in order to reach a sound ruling on the non-payment of zakāh. The researcher concluded the permissibility of the non-payment right of the zakāh due. Hence, based on maqāṣid related to zakāh, it is permissible to give out zakāh of agricultural and livestock products in cash instead the prescribed obligation, and that it is also permissible to pay zakāh in the form of assets for commercial offers instead of cash. The academic value of the study lies in its demonstration of the possibility of finding a rationale for an alternative to zakāh payment in cash, which is consistent with maqāṣid. By doing so, the zakāh benefactor would assume a social responsibility towards the needy, allowing the zakāh recipient to make ends meet and preserve his or her dignity.